Exploring the Notion of Literacy Within Physical Literacy: A Discussion Paper - Durden-Myers, Elizabeth J.; Bartle, Gillian; Whitehead, Margaret E.; Dhillon, Karamjeet K. (Frontiers in Sports and Active Living, 2022)
The concept of physical literacy is continuing to gain traction internationally. This increasing interest has also given rise to concerns about the use, interpretation and meaning of the term “literacy” within the context of physical literacy. This paper explores the development of the terms literate, illiterate, literacy, and illiteracy identifying their historical origin and contemporary meaning. This provides the backdrop to explore the use of the term literacy within the context of physical literacy. In the final part of this introductory section the recent popularity of the literacies movement is explored. Our discussion identifies key intersections and areas of tension associated with the use, interpretation and meaning of literacy in the context of physical literacy. We adopt Whitehead's philosophy of physical literacy and discussion is informed further by Derrida's notion of differance, and Barad's challenge to singular representations of concepts. Once harnessing these concepts, we reach a juncture of an in-between space; entry points of nonidentity (sameness) and points where multiple effects of difference are created. Key discussion topics include: discourse, language and interpretations of literacy; in/tangibility of literacy; capturing literacy; literacy as a process or a product; connotations of the terms literate and illiterate; neoliberalism and literacy and finally literacy as learning. We believe that when understood as the productive and meaningful interaction with/in/through the world, literacy is still the appropriate term within the context of physical literacy. Our discussion leads us to conclude that as embodied individuals, physical literacy is often the literacy through which other literacies have to pass. Through physical activity individuals can not only nurture their own physical literacy but also contribute toward a global or holistic literacy that helps us navigate, connect and make sense of ourselves, others and the world around us. However, the paper acknowledges that this meaning is not always grasped with the historical understanding of literacy as well as it's translations into other languages presenting challenges in articulating the intended use, meaning and connotations of the contemporary understanding of physical literacy.